Roots and Panicles of the C4 Model Grasses Setaria viridis (L). and S. pumila Host Distinct Bacterial Assemblages With Core Taxa Conserved Across Host Genotypes and Sampling Sites - Escobar Rodríguez, Carolina; Mitter, Birgit; Antonielli, Livio; Trognitz, Friederike; Compant, Stéphane; Sessitsch, Angela (Frontiers in Microbiology, 2018)
Virtually all studied plant tissues are internally inhabited by endophytes. Due to their relevance for plant growth and health, bacterial microbiota of crop plants have been broadly studied. In plant microbiome research the root is the most frequently addressed environment, whereas the ecology of microbiota associated with reproductive organs still demands investigation. In this work, we chose the model grasses Setaria viridis and Setaria pumila to better understand the drivers shaping bacterial communities associated with panicles (representing a reproductive organ) as compared to those associated with roots. We collected wild individuals of both grass species from 20 different locations across Austria and investigated the bacterial assemblages within roots and ripe grain-harboring panicles by 16S rRNA gene-based Illumina sequencing. Furthermore, plant samples were subjected to genotyping by genetic diversity-focused Genotyping by Sequencing. Overall, roots hosted more diverse microbiota than panicles. Both the plant organ and sampling site significantly shaped the root and panicle-associated microbiota, whereas the host genotype only affected root communities. In terms of community structure, root-specific assemblages were highly diverse and consisted of conserved bacterial taxa. In contrast, panicle-specific communities were governed by Gammaproteobacteria, were less diverse and highly origin-dependent. Among OTUs found in both plant tissues, relative abundances of Gammaproteobacteria were higher in panicles, whereas Rhizobiales dominated root communities. We further identified core and non-core taxa within samples of both Setaria species. Non-core taxa included members of the Saccharibacteria and Legionelalles, while core communities encompassed eleven OTUs of seven bacterial orders, together with a set of ten panicle-enriched OTUs. These communities were widespread across root and panicle samples from all locations, hinting towards an evolved form of mutualism through potential vertical transmission of these taxa within Setaria species.